Looking through translation: the importation of Chick lit in Turkey via translations and/or rewritings - Canseven, Cansu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This study explores the role that translation has played in the introduction and importation of chick lit as a literary genre in the Turkish literary system. The study acknowledges chick lit as a literary genre and presents the characteristics of chick lit as well as its position within the feminist history and its relation with women’s literature in the past. So as to investigate the role of Turkish translations of chick lit novels in introducing the genre into the Turkish literary polysystem, the translated chick lit novels in Turkey are descriptively examined year by year and notes are made regarding the publishing houses. The increase and decrease in the number of translated chick lit novels in years are observed and explained with respect to the marketing strategies of publishing houses and the appearance of the attempts for producing the first Turkish chick lit novel. Through the textual and paratextual analysis of the translations of Sophie Kinsella’s Shopaholic series and Ekin Atalar’s Selindrella series, the study reveals the similarities between the two and considers the latter as a “rewriting” of the former. In addition, the study presents a textual and paratextual analysis of Kocan Kadar Konuş by Şebnem Burcuoğlu to demonstrate that this book is the first example of “full import” of chick lit in Turkey.
Keywords: Chick lit -- Authorship.